2013
DOI: 10.1055/s-0033-1349721
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AlloMax Acellular Dermal Matrix for Objective Collagen Deposition

Abstract: Acellular dermal matrix products are popular in various aspects of surgical reconstruction including hernia repairs and breast reconstructions. The goal of this study was to determine quantitative collagen weights of AlloMax (C. R. Bard, Inc. [Davol], Warwick, RI) and of contralateral dermis for composition comparison. A rehydrated sample of AlloMax was subcutaneously implanted on the dorsum of 18 male Wistar rats. Rats were randomly assigned to groups on the basis of in vivo implant time: 1, 3, and 6 weeks. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Collagen organization and neovascularization in different types of ADM products have been proved by many studies 21,22 . In this study, we observed a higher grade of vascularization, fibroblast spreading, and collagen organization in ADM than CPD samples.…”
Section: Discussionmentioning
confidence: 98%
“…Collagen organization and neovascularization in different types of ADM products have been proved by many studies 21,22 . In this study, we observed a higher grade of vascularization, fibroblast spreading, and collagen organization in ADM than CPD samples.…”
Section: Discussionmentioning
confidence: 98%
“…Xenogenic (porcine) acellular dermal matrix (XADM) is made by using physical and chemical methods to remove the skin that causes cellular components of immune response and to retain the dermal frame. [9][10][11][12][13] XADM can effectively reduce rejection response in the patients after allograft, 14,15 because XADM is very similar to the real human acellular dermal matrix. Therefore, XADM might be used as human acellular dermal matrix substitutes.…”
mentioning
confidence: 99%